2018
DOI: 10.1167/iovs.18-25175
|View full text |Cite
|
Sign up to set email alerts
|

Altered Signaling Pathways in Aniridia-Related Keratopathy

Abstract: PURPOSE. To study the Notch1, Wnt/beta-catenin, sonic hedgehog (SHH), and mammalian target of rapamycin (mTOR) cell signaling pathways in naïve and surgically treated corneas of aniridia cases with advanced aniridia-related keratopathy (ARK). METHODS.Two naïve corneal buttons from patients with advanced ARK submitted to penetrating keratoplasty for the first time, one corneal button from an ARK patient that had undergone a keratolimbal allograft (KLAL), two corneal buttons from ARK patients who had previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(43 citation statements)
references
References 72 publications
5
38
0
Order By: Relevance
“…This cell signaling pathway has a very diverse 32 and its presence is enhanced in the epithelium and pannus of corneas with advanced ARK. 7 In the present study we showed that in fetal corneas at 10-11 wg and 20 wg, Wnt5a, and Wnt7a were abundantly identified in the corneal epithelial cells and stroma, whereas their presence was practically limited to the epithelium in normal adult corneas, as assessed by immunostaining. Upregulation of this signaling pathway in fetal corneas (as shown by both immunolabelling and gene expression analysis), was similar to what has been described in other ocular tissues during eye development.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…This cell signaling pathway has a very diverse 32 and its presence is enhanced in the epithelium and pannus of corneas with advanced ARK. 7 In the present study we showed that in fetal corneas at 10-11 wg and 20 wg, Wnt5a, and Wnt7a were abundantly identified in the corneal epithelial cells and stroma, whereas their presence was practically limited to the epithelium in normal adult corneas, as assessed by immunostaining. Upregulation of this signaling pathway in fetal corneas (as shown by both immunolabelling and gene expression analysis), was similar to what has been described in other ocular tissues during eye development.…”
Section: Discussionsupporting
confidence: 52%
“…19 We have previously shown that Dlk1 activation is increased in ARK corneal epithelial cells and stroma. 7 Numb, another important negative regulator of Notch1, is also upregulated in ARK corneas. 7 Determination of limbal stem cell fate is regulated by the Notch1 and Wnt/β-catenin signaling pathways and are essential during normal tissue development and regeneration.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations